La capacidad estatal en el control del tránsito vehicular en Lima e Ica en los años 2015-2016 - Zanabria Angulo, Victor Jose (2017)
Peruvian society recognizes two major problems that affect citizen insecurity and road insecurity, although these problems are seen daily on the streets, an analysis of what is related with them hasn´t been concluded and because the Peruvian state has no authority to control their factors of existence. This study analyzes the problem about state competition in order to control traffic, understanding that it is a public policy, which as such it looks for a problem about the society and it faces similar problems in the central government as in hobbies. As it´s detailed in this context, the problem is national, however, the capacities are diverse and diffuse, there is no consensus for its improvement and much less exist articulation or coordination in order to strengthen the authority acts and improve state capacities, therefore, this study seeks to analyze the problem determines the limitations of the policy and contribute to its solution